INOVASI SISTEM PEMERIKSAAN UJIAN SELEKSI CALON MAHASISWA BARU DI POLITEKNIK NEGERI UJUNG PANDANG - Dzulmukmin, Andi Abdul; Tungadi, Eddy; Abduh , Ibrahim (Journal of Informatics and Computer Engineering Research, 2024)
The inspection system for the entrance exam to the state polytechnic in Ujung Pandang is a process for checking participant computer answer sheets (LJK) to obtain the scores of participants who took the exam so that it becomes a benchmark for participants' graduation of the desired study program. The previous UMPN inspection system had drawbacks, namely the program inspection system still needed to be developed in terms of accuracy and effectiveness. Designing an FSI inspection program that has high accuracy requires data collection such as FSI along with references to similar inspection programs. The LJK inspection program uses the python language with the image processing library, namely openCV. LJK will be scanned and produce 100dpi and 200dpi LJK images which will be tested in the FSI inspection program. Based on the program testing conducted, it is recommended to use a 15x15 pixel resolution of 100dpi with an average accuracy of 99.31% and for a 200dpi resolution it is recommended to use 30x30 pixels with an average accuracy of 99.98%.